Local stress distribution in composites for pulled-out fibers with axially varying bonding - Igor V. Andrianov (5483624) (2022)
We present a study on the local stress distribution in a composite for a single-fiber pulled-out model. We consider an interphase between a fiber of finite length and the matrix, and we take into account varying bonding conditions in the axial direction between the fiber and the interphase and between the interphase and the matrix. Bonding is modeled by a modification of the classical spring-layer model, in which the quality of bonding between two constituents is quantified by a proportionality constant that describes the ratio of the displacements to the acting shear stresses in an interface. The problem is studied for linear elastic and for viscoelastic problems by the means of the elastic–viscoelastic correspondence principle. In numerical examples, we illustrate the development of the normal stresses in the constituents and of the interfacial shear stresses for different bonding conditions as well as for viscoelastic creep in the matrix. Other Information Published in: Acta Mechanica License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s00707-020-02634-6